The dynamics of local factionalism in the first distric of Iloilo and its significance to the National Party System. - Palmares, Louie Mae P
This study is an introspection on the dynamics of factions in the First District of Iloilo in 1980, 1992 and 1998 elections. This study explores and analyzes factional dynamics in line with Carl Lande's theory on the reciprocal-causal relationship between the national party and local faction., This study was conducted from October 2003 to February 2004 in the First District of Iloilo which is composed of seven (7) municipalities namely: Oton, Tigbauan, Guimbal, Tubungan, Igbaras, Miag-ao and San Joaquin. Structured and non-structured interview schedules were utilized to gather related information from twenty-six (26) respondents who participated in varying degrees during the 1980, 1992 and 1998 elections. Persons who did not participated directly in the elections but have been part of the factions were also interviewed. Documents from COMELEC, Manila as well as Municipal Planning and Development Office (MPDO) of the seven municipalities, articles from archival research and library materials were also utilized. There was no election contest to divide the First District into two or more factions during the 1980 elction. The 1992 and 1998 elections however, was characterized by factionalism in the district. The First District was divided into two factions: the Pro-Garin and the Anti-Garin factions. These local factions exist to serve as election machinery of the national parties and of candidates for congressional post. Support for national party does not strictly follow partisan considerations but availability of campaign funds and other prospective rewards in the event of electoral victory by Presidential candidates. While factions and parties exist for mutual coordination, there is no reciprocal-causal relationship that exist between them.